Challenges and Strategies to Strengthen Diabetes Prevention Programmes in Bangladesh - Nawar Duti, Nanziba; Ashraf, Musfiqa; Parvin, Naznin; Zaohara, Joynab; Hanif, Abu; Al Masood, Mohammad Abdullah; Kaium, Abdul; Ullah, Lokiat; Sharmin, Nusrat; Sultana Faria, Sabrina (Medicine Today, 2025)
Accelerated urbanization, changing lifestyle, and growing health inequality have all contributed towards Bangladesh's diabetes burden unfolding as a serious public health emergency. Structural, social, and policy-level impediments to the effective prevention and control of diabetes in the country are critically examined in this research. Despite the recognition of the threat of non-communicable disease (NCD) and of diabetes at the national programs and policy levels, implementation has been patchy and disproportionately concentrated in urban areas. Inequities are compounded by an un-integrated healthcare system, lack of funding, substandard primary care centers, and a severe shortage of trained staff. This paper highlights the intricacies of these barriers, various social determinants of health through to policy intransigence and digital divides, and the need for a multisectoral, equity-oriented, and integrated response. The potential of public-private partnerships, digital health innovations, and community interventions is examined in the context of Sustainable Development Goal 3 (SDG 3). Drawing from a close integration of policy briefs, epidemiological data, and the subject literature, this paper proffers strategic recommendations to augment the agenda for diabetes prevention in Bangladesh. It recommends scaling up primary prevention, capacity development, and reorientation of the health system towards chronic disease management to reduce morbidity, mortality, and socioeconomic consequences of diabetes. Medicine Today 2025, Vol.37 (2): 274-278